Efficacy of noncarbapenem therapy for the treatment of ceftriaxone-resistant Enterobacterales outside the urinary tract - Ethan P. Rausch; Kevin Alby; William Wilson (Cambridge University Press, 2024)
Abstract Objective: To determine the safety of noncarbapenem versus carbapenem antibiotics for treatment of adults with documented infection caused by ceftriaxone-resistant infections outside the urinary tract. Design: Retrospective cohort of adult patients with a documented infection caused by an extended-spectrum β-lactamase (ESBL)-producing organism isolated between January 2018 and October 2021. Setting: An academic tertiary-care center. Patients: Adult patients with a documented infection caused by an ESBL-producing organism outside the urinary tract. Methods: The primary outcome was a composite of treatment failure defined as 30-day mortality, 30-day readmission, microbiological recurrence, and/or clinical worsening requiring antibiotic change. Secondary outcomes included differentiation of primary composite components and postantibiotic Clostridioides difficile infection (CDI). Results: This study included 130 patients. The primary source of infections were bloodstream (67.7%) and caused by Escherichia coli (81.5%). Overall, 101 patients received carbapenem therapy and 29 received noncarbapenem therapy (NCT). NCT was comprised of mainly fluoroquinolones (18 of 29) followed by cefepime (7 of 29). Patients receiving NCT had shorter hospital stays (median, 7 days vs 9 days) and were more often discharged on antibiotics (79.3% vs 50.5%). We did not detect a significant difference in the primary composite outcome of treatment failure for carbapenem (23.8%) versus noncarbapenem treatment (24.2%; P = .967). Secondary outcomes included a numerically higher 30-day mortality rate in the noncarbapenem group compared to the carbapenem group: 4 (13.8%) of 29 versus 4 (3.9%) of 101. We did not detect a difference in rates of CDI. Conclusion: Noncarbapenem therapy may play a role for certain patients with infections caused by ESBL-producing organisms.